# HG changeset patch # User Eugen Sawin # Date 1309110372 -7200 # Node ID a20bf59d17757e15ce9022556537d344f202a143 # Parent 1796e8ba2c1e1f706d654ed8addfaea8fb02c5fe Added latest unfinished exercise. diff -r 1796e8ba2c1e -r a20bf59d1775 tex/theory1_ex6.tex --- /dev/null Thu Jan 01 00:00:00 1970 +0000 +++ b/tex/theory1_ex6.tex Sun Jun 26 19:46:12 2011 +0200 @@ -0,0 +1,75 @@ +\documentclass[a4paper, 10pt, pagesize, smallheadings]{article} +\usepackage{graphicx} +%\usepackage[latin1]{inputenc} +\usepackage{amsmath, amsthm, amssymb} +\usepackage{typearea} +\usepackage{algorithm} +\usepackage{algorithmic} +\usepackage{fullpage} +\usepackage{mathtools} +\usepackage[all]{xy} +\title{Theory I, Sheet 6 Solution} +\author{Eugen Sawin} +\renewcommand{\familydefault}{\sfdefault} +\include{pythonlisting} + +\pagestyle{empty} +\begin{document} +\maketitle + +\section*{Exercise 6.1} +\[\Phi(T) = |2 \cdot num - size|\] +\[a_i = \Phi_i - \Phi_{i-1} + t_i\] +\[a_i = |2k_i - s_i| - |2k_{i-1} - s_{i-1}| + t_i\] +We calculate the amortized costs for the two distinct cases. + +\subsection*{case 1 (no contraction required)} +Since there was no contraction we know that $s_i = s_{i-1}$ and it follows that $\frac{1}{3}s_i \leq k_i \leq s_i - 1$. Since we have deleted an element we know that $k_i = k_{i-1} - 1$. Because we have only removed an element it follows that $t_i = 1$. We reduce the formula using these substitutions. +\[a_i = |2k_i - s_i| - |2k_{i-1} - s_{i-1}| + t_i\] +\[= |2k_i - s_i| - |2k_i + 2 - s_i| + 1\] +Now we look for the minimum and maximum value of the above formula. We choose the obvious values for $k_i$ which are within valid range. +\[(k_i = \frac{s_i}{2}) \implies a_i = |s_i - s_i| - |s_i - s_i + 2| + 1\] +\[= 0 - 2 + 1 = -1\] + +\[(k_i = \frac{s_i}{2} - 1) \implies a_i = |s_i - 2 - s_i| - |s_i - 2 - s_i + 2| + 1\] +\[= 2 - 0 + 1 = 3\] + +\[\implies -1 \leq a_i \leq 3\] +\subsection*{case 2 (contraction required)} +Since there was a contraction we know that $s_i = \frac{2}{3}s_{i-1}$ and it follows that $k_i = \frac{1}{3}s_{i-1} - 1$. Since we have deleted an element we know that $k_i = k_{i-1} - 1$. Because we have removed an element and additionally copied all previously contained elements it follows that $t_i = \frac{1}{3}s_{i-1} + 1$. We reduce the formula again using these substitutions. +\[a_i = |2k_i - s_i| - |2k_{i-1} - s_{i-1}| + t_i\] +\[= |2k_i - \frac{2}{3}s_{i-1}| - |2k_i + 2 - s_{i-1}| + t_i\] +\[= |\frac{2}{3}s_{i-1} - 2 - \frac{2}{3}s_{i-1}| - |\frac{2}{3}s_{i-1} - 2 + 2 - s_{i-1}| + \frac{1}{3}s_{i-1} + 1\] +\[= |-2| - |-\frac{1}{3}s_{i-1}| + \frac{1}{3}s_{i-1} + 1\] +\[(\text{since } s_{i-1} > 0) \implies a_i = 2 - \frac{1}{3}s_{i-1} + \frac{1}{3}s_{i-1} + 1\] +\[= 2 + 1 = 3 \leq 3\] +By calculating the amortized costs for both Table-Delete cases, we have have shown that the amortized costs are bounded by constant 3. \qed + +\section*{Exercise 6.2} +\[\alpha = \frac{k}{s}\] +\[\Phi(T) = +\left\{ +\begin{array}{l l} + 2k-s & \text{if $\alpha \geq \frac{1}{2}$}\\ + \frac{s}{2}-k & \text{if $\alpha < \frac{1}{2}$}\\ +\end{array} \right.\] + +We show $\sum a_i \geq \sum t_i$. +\[a_i = \Phi_i - \Phi_{i-1} + t_i\] +\[\implies \sum_{i=1}^{n}a_i = \sum_{i=1}^{n}\Phi_i - \Phi_{i-1} + t_i\] +\[= \sum_{i=1}^{n}\Phi_i - \sum_{i=0}^{n-1}\Phi_i + \sum_{i=1}^{n}t_i\] +\[= \Phi_n - \Phi_0 + \sum_{i=1}^{n}t_i\] + +By definition we know that $\Phi_0 = -1$ and since $2k-s \geq 0$ for $\alpha \geq \frac{1}{2}$ and $\frac{s}{2}-k \geq 0$ for $\alpha < \frac{1}{2}$ it follows that $\Phi_n - \Phi_0 >= 0$. +\[\implies \Phi_n - \Phi_0 + \sum_{i=1}^{n}t_i \geq \sum t_i\]\qed + +\section*{Exercise 6.3} +We show +\[\sum_{k=2}^{n-1}k\,lg\,k \leq \frac{1}{2}n^2\,lg\,n - \frac{1}{8}n^2\] +\[\sum_{k=2}^{n-1}k\,lg\,k = \sum_{k=2}^{\lceil \frac{n}{2} \rceil - 1}k\,lg\,k\ + \sum_{k=\lceil \frac{n}{2} \rceil}^{n-1}k\,lg\,k\] +\[\leq \sum_{k=2}^{\lceil \frac{n}{2} \rceil - 1}k\,lg\,\lceil \frac{n}{2} \rceil + \sum_{k=\lceil \frac{n}{2} \rceil}^{n-1}k\,lg\,n\] +\[= lg\,\lceil \frac{n}{2} \rceil \sum_{k=2}^{\lceil \frac{n}{2} \rceil - 1}k + lg\,n \sum_{k=\lceil \frac{n}{2} \rceil}^{n-1}k\] +\[= (lg\,n - lg\,2) \sum_{k=2}^{\lceil \frac{n}{2} \rceil - 1}k + lg\,n \sum_{k=\lceil \frac{n}{2} \rceil}^{n-1}k\] +\[= lg\,n \sum_{k=2}^{\lceil \frac{n}{2} \rceil - 1}k - \sum_{k=2}^{\lceil \frac{n}{2} \rceil - 1}k + lg\,n \sum_{k=\lceil \frac{n}{2} \rceil}^{n-1}k\] +\[= lg\,n \frac{(n-1)(n-2)}{2} - \] +\end{document}